Study of correlation of various metabolic abnormalities in patients of metabolic syndrome with abnormal thyroid functions and ultrasonography from Central India - Upadhyay, Shubham; Jhavar, Dharmendra; Patel, Naresh Kumar; Chouhan, Rajesh; Khalwadekar, Ambar (International Journal of Advances in Medicine, 2021)
Background: Metabolic syndrome is a cluster of various clinical and biochemical abnormalities. The thyroid hormone has influence on almost each and every cell of various organs in the body. Its deficiency or excess is likely to have various metabolic abnormalities and structural changes in thyroid gland may correlate with abnormal thyroid function test. Methods: This cross sectional observational study was conducted in 100 consecutive patients of metabolic syndrome from October 2013 to October 2014 at MGM medical college and MY hospital Indore, Madhya Pradesh, India from one year of study duration and both outdoor and in patients were included in this study. Results: In this study, 24 (24%) patients were pre-hypertensive. A 42 (42%) and 13 (13%) patients had stage I and stage II hypertension respectively. 78 (78%) patients had FBS more than 100 mg/dl and out of these patients, 61 patients had DM type 2 with FBS more than 125 mg/dl. TG was more than 150 mg/dl in 65 (65%) patients. Serum HDL level was low in 30 males and 52 females. USG thyroid findings in patients with thyroid dysfunction (24), were within normal limit, thyroiditis, thyroid adenoma, benign thyroid nodule, multinodular goiter, colloid cyst, and neoplastic lesion in 62.5%, 8.3%, 8.3%, 4.2%, 8.3%, 4.2%, and 4.2% respectively. Conclusions: Prevalence of thyroid dysfunctions is more common in metabolic syndrome patients. All metabolic syndrome patients can be evaluated by thyroid function tests and ultrasonography to diagnose thyroid dysfunctions in early stages.